Human resource development in Thailand. - Chin, Colin. (2008)
This dissertation is a synergistic product of many minds that have keen interest in human resource development in Thailand. We are grateful for the wisdom of these specialists through their speeches and resources provided during our visit to Thailand. In the preparation of the dissertation itself we feel a deep sense of gratitude to those members of the following organisations in Thailand that we met during our visit; NIDA, Kenan Institute, Department of Vocational Education, Department of Skill Development, Office of the Board of Investment, Sahaviriya Steel, Oji Paper (Thailand) Limited, Bank of Thailand, and the Institute of East Asia Studies of Thammasat University. Without the in-depth knowledge and wisdom of these people in the areas of education and training in Thailand, it would not be possible for us to gain comprehensive views of human resource development in Thailand.